2020
DOI: 10.1097/ijg.0000000000001771
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Airborne COVID-19 Transmission While Performing Humphrey Visual Field Testing

Abstract: Precis: Designing and demonstrating an experiment that shows the risk of airborne transmission of COVID-19 between patients having visual fields analyzed is low. Purpose: The aim was to investigate the possibility of airborne transmission of COVID-19 during Humphrey visual field testing in a real-world scenario. Methods: A particle counter was placed within the bowl of Humphrey visual field analyzer (HFA) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…This confirms the manufacturer's claim that the ventilation current of the HFA perimeters pushes air from within the bowl past the patient. It is unlikely that whether or not a patient wears a mask during testing itself has any bearing on airborne transmission 6 …”
Section: Practice In the Covid Eramentioning
confidence: 99%
See 2 more Smart Citations
“…This confirms the manufacturer's claim that the ventilation current of the HFA perimeters pushes air from within the bowl past the patient. It is unlikely that whether or not a patient wears a mask during testing itself has any bearing on airborne transmission 6 …”
Section: Practice In the Covid Eramentioning
confidence: 99%
“…Fortunately, there are studies to suggest that airborne transmission of COVID-19 within the field analyser bowl was low. 6 Jain et al showed that particulate count in suspension within the bowl of a Humphrey visual field analyser (HFA) was significantly reduced by the activation of the cooling fans present within the machine and, crucially, that this particulate count is unaffected following use of the machine by a patient who is not wearing a mask. This confirms the manufacturer's claim that the ventilation current of the HFA perimeters pushes air from within the bowl past the patient.…”
Section: Practice In the Covid Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Наконец, немаловажен вопрос о риске заражения SARS-CoV-2 во время офтальмологических обследований и операций. Так, в литературе обсуждается риск заражения данной инфекцией при тонометрии [5,42] и периметрии [43].…”
unclassified
“…2 We would also like to know the range of refractive errors among the study population, as myopic patients show a significant influence of refraction on the differential light sensitivity in the peripheral visual field, whereas hyperopic eyes show in the central visual fields. 3 Ma et al, 4 in their paper, demonstrated an efficacy of 97.14% and 95.15% for surgical and homemade (made of 4-layer kitchen paper and 1-layer cloth) masks respectively in blocking severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. Osterholm and colleagues reported the physical properties of cloth mask and the frequency, effectiveness of cleaning cloth masks.…”
mentioning
confidence: 99%